(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background: Magnetic resonance imaging (MRI) detects soft tissue pathologies and lumbar disc illnesses such as bulging, herniation, spinal stenosis, and vertebral abnormalities. Three-dimensional (3D) isotropic MRI provides several benefits over two-dimensional (2D) turbo spin-echo sequences for musculoskeletal imaging. Objective: To compare the image quality of 2D T2-weighted turbo spin-echo (2D T2W TSE) sequences to 3D T2-weighted turbo spin-echo (3D T2W TSE) sequences and estimate how physical parameters of patients, including age and sex, may impact the outcome of medical imaging. Methods: Seventy patients with lumbar spine problems (mean age below 50) were examined. MRI scans were obtained with 2D T2W TSE and 3D T2W TSE sequences. Parameters assessed included image contrast, signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), and signal intensity, calculated using a region-of-interest tool. Results: The findings demonstrated that 2D T2W TSE images exhibited significantly higher mean (230.59±64.4) signal intensity values, and greater signal intensity variability (2.92±0.61) than 3D T2W TSE images. Conversely, 3D T2W TSE images outperformed their 2D counterparts in signal-to-noise ratio (82.93±31.51) and contrast-to-noise ratio (40.55±14.95). A strong negative correlation was observed between age and both the mean signal intensity and SNR in 2D T2W TSE images. No significant association was found between age and any characteristics of 3D T2W TSE images. Furthermore, sex showed no significant correlation with any features of 2D or 3D T2W TSE images. Conclusion: The research found increased signal intensity in 2D T2W TSE images and higher SNR and CNR in 3D T2W TSE images. These data imply that age may affect signal intensity measures from 2D T2W images, lowering image quality in older individuals. The lack of a significant link between age and 3D T2W TSE parameters shows that age-related changes may not impact 3D T2W TSE images. Keywords: Magnetic resonance imaging, lumbar spine, 2D sequence, 3D sequence, image quality. Citation: Awad NW, Ahmed RS, Zghair MA. Comparative diagnostic efficacy of 3D vs 2D T2-weighted MRI in assessing lumbar spine pathologies. Iraqi JMS. 2025; 23(1): 147-154. doi: 10.22578/IJMS.23.1.17